2016
DOI: 10.1037/dhe0000031
|View full text |Cite
|
Sign up to set email alerts
|

College students with disabilities redefine activism: Self-advocacy, storytelling, and collective action.

Abstract: Despite rapid growth in the numbers of students with disabilities enrolling in higher education, there is limited research about their experiences in colleges and universities, and information about their collegiate activism is even more limited. Through a constructivist grounded theory study of 59 college students and recent graduates, we demonstrate the connection between activism and purpose in the lives of students with disabilities. Our findings suggest advocacy skills and activist tendencies were sociali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 51 publications
1
41
0
1
Order By: Relevance
“…Ultimately, however, we must note that we do not believe this study to be exceptionally unique. While it is true that there is limited research on this topic (Kimball et al., ), our study provided robust information about many facets of students’ experiences on campus—including their social lives, experiences in residential halls, thoughts about disability services, comments on instructor behaviors, and more. The expansive nature of constructivist qualitative work means that it will almost always produce a broader range of findings than intended: it has a way of showing the interconnectedness of otherwise disparate experiences.…”
Section: Concluding Thoughtsmentioning
confidence: 89%
See 2 more Smart Citations
“…Ultimately, however, we must note that we do not believe this study to be exceptionally unique. While it is true that there is limited research on this topic (Kimball et al., ), our study provided robust information about many facets of students’ experiences on campus—including their social lives, experiences in residential halls, thoughts about disability services, comments on instructor behaviors, and more. The expansive nature of constructivist qualitative work means that it will almost always produce a broader range of findings than intended: it has a way of showing the interconnectedness of otherwise disparate experiences.…”
Section: Concluding Thoughtsmentioning
confidence: 89%
“…Even in leaving the basketball team, however, this participant also revealed that she had learned to identify situations that were maladaptive for her success and to remove herself from them, which can be a key form of self‐determination for people with disabilities (Kimball, Moore, Vaccaro, Troiano, & Newman, ).…”
Section: A More Nuanced Understanding Of Disability and Athleticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kimball, Moore, Vaccaro, Troiano, and Newman () found that college students with disabilities were often not recognized as activists or student leaders despite extensive action on and off campus. By expanding the definition of activism and reimagining what leadership looked like, Kimball et al.…”
Section: Cultural Social Justice and Inclusion Competencies: An Ovementioning
confidence: 99%
“…In "From Margins to Mainstream: Social Media as a Tool for Campus Sexual Violence Activism, " Linder, Myers, Riggle, and Lacy (2016) use Internet-related ethnography to call attention to the growing role of social media in student organizing, specifically addressing campus sexual violence. Kimball, Moore, Vaccaro, Troiano, and Newman (2016) in "College Students with Disabilities Redefine Activism: Self-Advocacy, Storytelling and Collective Action" rely on a constructivist grounded theory approach to offer important insights into the ways in which students with disabilities challenge traditional conceptions of student activism. In "'The Poor Kids' Table': Organizing Around an Invisible and Stigmatized Identity in Flux," Warnock and Hurst (2016) utilize qualitative data from 16 semistructured interviews to examine the formation and maintenance of a support group involving low-income, first-generation, and/or working-class students (LIFGWC); a key finding notes that LIFGWC students differed in their comfort level in terms of engaging in social class based campus activism.…”
Section: Special Issue On Student Activism: What Followsmentioning
confidence: 99%